1987
DOI: 10.1099/00221287-133-10-2915
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Amplified Expression in Streptomyces Iividans of the Gene Encoding the Extracellular  -Lactamase from Streptumyces cacaoi

Abstract: A 19 kb SphI DNA fragment containing the gene for the extracellular active-site serine beta-lactamase of Streptomyces cacaoi KCC-SO352 was cloned in Streptomyces lividans TK24 using the high-copy-number plasmid pIJ702 as vector. A 30-fold higher yield of beta-lactamase was obtained from S. lividans strain ML1, carrying the recombinant plasmid pDML51, than from S. cacaoi grown under optimal production conditions. In all respects (molecular mass, isoelectric point, kinetics of inhibition by beta-iodopenicillanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…It was previously shown that such mutated boxes are unable to form DNA-protein binding complexes in vitro (Giannotta et al 1996). Transcriptional fusions were con- structed between the native and mutated promoter regions of xlnC and the S. cacaoi b-lactamase gene, blaL (Lenzini et al 1987). These fusions were then inserted into the multicopy plasmid pIJ702 to yield pDML639, pDML639mB2, pDML639mB3 and pDML639mB23 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that such mutated boxes are unable to form DNA-protein binding complexes in vitro (Giannotta et al 1996). Transcriptional fusions were con- structed between the native and mutated promoter regions of xlnC and the S. cacaoi b-lactamase gene, blaL (Lenzini et al 1987). These fusions were then inserted into the multicopy plasmid pIJ702 to yield pDML639, pDML639mB2, pDML639mB3 and pDML639mB23 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…pIJ385 (13) and pIJ486 (40) were from T. Kieser and M. J. Bibb (John Innes Institute). pSL1 (27,39), pDML51, pDML52, pMCP38, and pMCP39 (20), and pMCP28 (25) were described previously. BamHI linker, Escherichia coli HB101 (3), and pUC18 (41) were from Takara Shuzo Co. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the gene encoding the P-lactamase of Streptomyces cacaoi (30) was cloned and sequenced (19,20). Experiments were then undertaken to identify the transcriptional start point and to explore the regulatory effects that upstream DNA sequences may exert on gene expression.…”
mentioning
confidence: 99%
“…When grown in the glycerol-casein medium containing 25 gg thiostrepton per ml, S. lividans TK24/pDML120 produced twice as much extracellular DD-peptidase/PBP as S. lividans TK24/ p D M L l l 0 (42mg versus 20.6rag/i), showing the increased efficiency of pDML] 20 compared to the original pDMLll0. Note that the growth conditions (120 h at 28 ° C) were optimal and identical for both strains and that S. lividans TK24/pIJ702 did not produce any detectable extracellular DD-peptidase or #-lactamase (Duez et al 1987;Lenzini et al 1987). (iv) Plasmid pDML129.…”
Section: Construction Of a Streptomyces Expression-secretion Vectormentioning
confidence: 99%
“…produce extracellular/~-lactamases and ~)D-peptidases/penicillin-binding proteins (PBPs) and several genes encoding these proteins, which all interact with penicillin, have been cloned (Dehottay et al 1986;Duez et al 1987;Lenzini et al 1987;Piron-Fraipont et al 1989) and sequenced (Duez et al 1987;Dehottay et al 1987;Lenzini et al 1988;Houba et al 1989). The nucleotide sequence containing the transcriptional, translational and secretory signals of the dac gene that encodes the DD-peptidase/ PBP of Streptomyces R61 has been used to construct a Streptomyces expression-secretion vector.…”
Section: Introductionmentioning
confidence: 99%